2018
DOI: 10.1111/jicd.12381
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical, microbiological, and genetic considerations in treatment of Chinese periodontal patients

Abstract: The aim of the present narrative review was to highlight considerations when treating Chinese patients with periodontal diseases. These considerations can be broadly categorized into anatomical, microbiological, and genetic considerations. Anatomical considerations are tooth‐related factors causing site‐specific issues, and these include incisal palatal groove, root concavities, three‐rooted permanent mandibular first molar, furcation entrance dimensions, cervical enamel projections, root trunk length, and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The average percentage of error prediction between molars and non‐molars showed a statistically significant difference ( p < .01). Further, upon statistical analysis, three possible reasons were revealed: (1) the mean amount of teeth at each position with an average baseline of PD ≥5 mm differed between the molars (387.5) and non‐molars (147.2) in test dataset; (2) molars were considered inferior treatment outcomes and worse prognosis due to anatomic factors such as presence of furcation, concavities on the root surfaces and cervical enamel projections 36,37 ; (3) and the unique anatomical characteristics of Chinese descendants can be another reason 38,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average percentage of error prediction between molars and non‐molars showed a statistically significant difference ( p < .01). Further, upon statistical analysis, three possible reasons were revealed: (1) the mean amount of teeth at each position with an average baseline of PD ≥5 mm differed between the molars (387.5) and non‐molars (147.2) in test dataset; (2) molars were considered inferior treatment outcomes and worse prognosis due to anatomic factors such as presence of furcation, concavities on the root surfaces and cervical enamel projections 36,37 ; (3) and the unique anatomical characteristics of Chinese descendants can be another reason 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…and non-molars (147.2) in test dataset; (2) molars were considered inferior treatment outcomes and worse prognosis due to anatomic factors such as presence of furcation, concavities on the root surfaces and cervical enamel projections 36,37 ; (3) and the unique anatomical characteristics of Chinese descendants can be another reason. 38,39 This study was the first site-level precise prediction model which was built on mass followed cohorts of Chinese patients treated for periodontitis. Results of this study reflect the real-world situation that the frequency of subjects with severe periodontitis (stage III or IV) was about 92%, much higher than previous finding in data from the Fourth National Oral Health Survey (2015-2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…It was found that more than half of people may have cervical enamel projection (CEP) in their molars [67]. Connective tissues are unable to attach to CEPs, and therefore CEPs have been implicated as a risk factor for the development of localized periodontitis [68]. In the 28 cases of paradental cyst that Craig et al [5] observed, 20 cases showed developing CEP or CEP extending from the enamel cementum to the bifurcation.…”
Section: Dental Anatomy Factorsmentioning
confidence: 99%
“…The bone loss that occurs within this space is known as furcation involvement [4]. The major factors for furcation involvement are greater plaque and calculus accumulation, improper brushing techniques, developmental abnormalities like cervical enamel projections, deep grooves on furcation area, anatomical positioning of tooth, and shorter roots (where earlier furcation involvement occurs) [5]. All the above cited factors will hamper the maintenance of furcation leading to poor oral hygiene, gingival inflammation and periodontal attachment loss cum bone loss sequentially [6].…”
Section: Introductionmentioning
confidence: 99%